Pengaruh Model Pembelajaran Terintegrasi Shared terhadap Hasil dan Motivasi Belajar pada Pokok Bahasan Sistem Sirkulasi Siswa Kelas XI di SMAN 4 Samarinda Tahun Pembelajaran 2025/2026 - Nur Zahra Al Azizah; Herliani Herliani; Sonja Verra Tinneke Lumowa; Elsje Theodora Maasawet (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to analyze the effect of the shared integrated learning model on student learning outcomes and motivation in the circulatory system topic in grade XI of SMAN 4 Samarinda. This study used a quasi-experimental method with a non-equivalent control group design and purposive sampling technique. The research sample consisted of 25 students in the experimental class and 25 students in the control class. The research instruments were a learning outcome test and a learning motivation questionnaire. Data analysis was conducted using the N-gain test and independent sample t-test at a significance level of α = 0.05. The results showed that the N-gain of learning outcomes in the experimental class was 0.61 (medium category) higher than the control class at 0.31 (low category). The N-gain of learning motivation in the experimental class was 0.20 (low category) also higher than the control class at 0.04 (very low category). The results of the hypothesis test showed a significance value <0.05, so the shared integrated learning model has a significant effect on student learning outcomes and motivation in the circulatory system topic.